Randomised sham-controlled trial of transcutaneous electrical stimulation in obstructive sleep apnoea. Issue 10 (19th July 2016) - Pengo, Martino F; Xiao, Sichang; Ratneswaran, Culadeeban; Reed, Kate; Shah, Nimish; Chen, Tao; Douiri, Abdel; Hart, Nicholas; Luo, Yuanming; Rafferty, Gerrard F; Rossi, Gian Paolo; Williams, Adrian; et al.
Abstract : Introduction: Obstructive sleep apnoea (OSA) is characterised by a loss of neuromuscular tone of the upper airway dilator muscles while asleep. This study investigated the effectiveness of transcutaneous electrical stimulation in patients with OSA. Patients and methods: This was a randomised, sham-controlled crossover trial using transcutaneous electrical stimulation of the upper airway dilator muscles in patients with confirmed OSA. Patients were randomly assigned to one night of sham stimulation and one night of active treatment. The primary outcome was the 4% oxygen desaturation index, responders were defined as patients with a reduction >25% in the oxygen desaturation index when compared with sham stimulation and/or with an index <5/hour in the active treatment night. Results: In 36 patients (age mean 50.8 (SD 11.2) years, male/female 30/6, body mass index median 29.6 (IQR 26.9–34.9) kg/m 2, Epworth Sleepiness Scale 10.5 (4.6) points, oxygen desaturation index median 25.7 (16.0–49.1)/hour, apnoea-hypopnoea index median 28.1 (19.0–57.0)/hour) the primary outcome measure improved when comparing sham stimulation (median 26.9 (17.5–39.5)/hour) with active treatment (median 19.5 (11.6–40.0)/hour; p=0.026), a modest reduction of the mean by 4.1 (95% CI −0.6 to 8.9)/hour. Secondary outcome parameters of patients' perception indicated that stimulation was well tolerated. Responders (47.2%) were predominantly from the mild-to-moderate OSA category. In this subgroup, the oxygen desaturation index was reduced by 10.0 (95% CI 3.9 to 16.0)/hour (p<0.001) and the apnoea-hypopnoea index was reduced by 9.1 (95% CI 2.0 to 16.2)/hour (p=0.004). Conclusion: Transcutaneous electrical stimulation of the pharyngeal dilators during a single night in patients with OSA improves upper airway obstruction and is well tolerated. Trial registration number: NCT01661712.